Association between oxidative balance score and kidney stone in United States adults: analysis from NHANES 2007-2018 - Ke, Runjiang; He, Youhua; Chen, Chaohao (Frontiers in Physiology, 2023)
Purpose: To investigate the relationship between the Oxidative Balance Score (OBS) and kidney stone risk using NHANES 2007-2018 data, and to explore potential mechanisms and populationspecific effects.Data from the NHANES 2007-2018 were analyzed. OBS was calculated based on 16 dietary components and 4 lifestyle components. Multivariate logistic regression was employed to investigate the relationship between OBS and kidney stone. Further stratified analyses were conducted to examine the associations across different subgroups.Results: A total of 19,799 participants were included in the study. There was a consistent inverse association between OBS and the risk of kidney stones (OR=0.97; 95% CI: 0.96-0.99). After dividing the participants into quartiles based on OBS, compared to the lowest quartile of OBS, the risk of kidney stones in the highest quartile of OBS was reduced by 33% (95% CI 0.50-0.89; P=0.002). This association was consistent across both dietary and lifestyle OBS scores. The protective effect of OBS was notably pronounced among Non-Hispanic White and Other race groups, and among individuals with a higher level of education. However, the association was not significant among individuals with diabetes.Conclusions: A higher OBS, indicating a balance skewed towards antioxidants, is associated with a reduced risk of kidney stones, especially among specific population subgroups. These findings underscore the potential role of oxidative balance in kidney stone pathogenesis and highlight the importance of considering individual and population-specific factors in future research and preventive strategies.